Explaining Inefficient Policy Instruments - de Gorter, Harry (World Bank, Washington, DC, 2017)
The purpose of this paper is to provide an overview of the literature on the political economy of policy instrument choice and relate it to the experiences in agriculture. The paper is therefore organized as follows. The second section provides a ranking of policies as to their transfer efficiency and determines the standard of evaluation, given that no policy is perfect in achieving its goals. The third section explores why political competition does not ensure that an efficient policy instrument is chosen. The following two sections explain the two key theories: enforcement and commitment problems in section four, and information and agency problems in section five. Section six presents the important Grossman-Helpman model of inefficient policy choice that falls outside these two general theories. Section seven describes how policy instrument choice in agriculture is often a discrete outcome in response to a crisis and therefore becomes path dependent, resulting in a status quo bias. Section eight describes how trade agreements can affect policy instrument choice. The final section gives some guidance as to the outstanding issues.